The Effect of Think-Talk-Write (TTW) Strategy on Students’ Writing Ability in Procedure Text at Grade Ten of SMA Swasta Taman Siswa Pematangsiantar - Angela Shakila Aurel Pane; Anita Sitanggang; David Berthony Manalu (International journal of technology and education research, 2026)
This research aimed to determine the effect of the Think–Talk–Write (TTW) strategy on students’ writing ability in procedure texts at the tenth grade of SMA Swasta Taman Siswa Pematangsiantar. The research focused on students’ ability in writing procedure texts related to traditional Sumatran food recipes. The students’ writing ability was assessed based on five aspects: content, organization, vocabulary, language use, and mechanics. This research applied a quantitative research method with a quasi-experimental design. The population of this research was the tenth-grade students of SMA Swasta Taman Siswa Pematangsiantar. The sample consisted of two classes, namely the experimental class and the control class. The experimental class was taught by using the Think–Talk–Write (TTW) strategy, while the control class was taught by using a conventional teaching strategy. The findings of the research showed that the students who were taught by using the Think–Talk–Write (TTW) strategy achieved better improvement in writing ability than those who were taught by using the conventional teaching strategy. The result indicated that the TTW strategy helped students generate ideas, organize procedural steps systematically, improve vocabulary usage, and apply grammatical structures more accurately in writing procedure texts.